Synthesis and characterization of nanosized ZnTiO3 doped with reduced graphene oxide (RGO). Issue 1 (February 2021) - Martinov, B L; Staneva, A D; Vlakhov, T E; Slavov, S; Dimitrov, D; Marinov, Y G; Hadjichristov, G B
Abstract: Composite materials based on nanosized zinc titanate (ZnTiO3 ) doped with reduced graphene oxide (RGO) were obtained by means of ultrasonically assisted precipitation. In these composites, the concentration of RGO nanopartiles was varied from 1 wt.% to 20 wt.%. The ZnTiO3 ceramic was produced by sol-gel method. RGO was prepared by a modified Hammers method and subsequent chemical reduction with sodium borohydride. Structural and phase characterization of the fabricated composites was performed by XRD, scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). It was identified that for all of the studied samples of the RGO/ZnTiO3 series, the two phases are uniformly distributed over the observed areas, which proves the formation of homogeneous nanocomposite materials. The electrical properties of the series of RGO/ZnTiO3 samples were characterized by complex electrochemical impedance spectroscopy (EIS) in the frequency range from 0.1 Hz to 1 MHz. The results obtained by EIS for the electrical conductance of RGO-doped ZnTiO3 as a function of the concentration of RGO nanoparticles were correlated with the data from structural studies.